TALKING STICK LEARNING MODEL IN FIQH CLASS VII AT SMP IT RAUDHATUL ANWAR KAPUAS KUALA - Zaenal Arifin; Agung Is Hardiyana Febry; Ali Ridho (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2021)
Abstract Learning model is a learning pattern that is designed in such a way, applied and evaluated systematically in order to achieve the learning goals effectively. This article discusses the application of the Talking Stick learning model for Toharoh Fiqh lessons for 7th grade students at SMP IT Raudhatul Anwar Kapuas Kuala Kapuas Regency, the supporting factors and obstacles in the application of this learning model. This research is a field research of a qualitative approach. After the data is collected and presented, the data is analyzed by using descriptive qualitative technique analysis. Inductive technique is used to draw conclusions. The application of Talking Stick learning model in Fiqh Subjects includes planning (Lesson Plan), compiling evaluation tools to measure student learning outcomes, preparing learning source and tools/media learning. In implementation, the teacher carries out pre-learning activities, steps of Talking sticks model learning, and closes well, and assessing by spreading question evaluation in the form of LKS individually for measuring students' ability to understand the material that has been explained.